Influência da síndrome da fragilidade, nível de atividade física e cognição no desempenho do teste de dupla tarefa - Rossi, Paulo Giusti (2016)
The frailty syndrome has been described as an important geriatric syndrome by being associated with an increased risk of functional decline, falls, institutionalization, hospitalization and death. In addition, some studies have found an association with cognitive decline and low level of physical activity. The study aims were (a) to verify the influence of frailty syndrome, level of physical activity and cognition on Timed Up and Go test (TUG) and Timed Up and Go associated with dual task (TUG-DT) performances; and (b) to compare TUG and TUG-DT performances between older adults who developed frailty syndrome. Sixty-four individuals were divided into frail, pre-frail and non-frail groups. The assessment consisted of cognition (ACE-R), physical activity level (triaxial accelerometer), isolated secondary task, TUG and TUG-DT. For statistical analysis, one-way ANOVA or Chi-square tests were used to compare groups. Multiple linear regression to identify variables that could predict the time performance in TUG and TUG-DT, and, ANCOVA to compare the three groups. Regarding the characteristics of the sample, the groups presented homogeneous, except gender, which showed more women in the pre-frail group. Significant differences in daily physical activity level were found in the frail group for energy expenditure, time sitting/lying, time standing, time stepping and step count variables. There were no differences in ACE-R total score, however, there was difference between the frail group and non-frail just in attention and orientation domain. The isolated secondary task was influenced cognition during its realization, but there were no differences between groups. TUG performance was not influenced by age, physical activity level or frailty, however, frail group differed from non-frail group in time and number of steps. Regarding the performance of the elderly in TUG-DT, cognition and age influenced the time of completion and number of steps, respectively, however, no differences were found between groups. The results show that the performance of the TUG is influenced by the presence of the frailty syndrome, age and of physical activity level and the performance of the TUG-DT is influenced by age and cognition.